Analisis Inovasi Tata Kelola Keuangan Desa melalui SISKEUDES (Sistem Keuangan Desa) di Desa Sindangheula - Angeli Ramadhani; Laeli Nur Khanifah; Dita Amalia; Siti Dinda Rahayu; Modella Raghel Monika (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study aims to evaluate and develop SISKEUDES implementation in Sindangheula Village through the lens of Everett M. Rogers' Diffusion of Innovation theory. Using a qualitative descriptive method, data were collected through interviews with the village head and financial affairs officer. The findings indicate that SISKEUDES has been adopted primarily due to its relative advantage in replacing manual systems, resulting in more structured and accountable financial management. However, the complexity of the system, particularly in terms of technical usage and cognitive adaptation, presents challenges for village apparatus with limited digital literacy. The study highlights that successful adoption depends not only on the innovation's superiority but also on institutional readiness and continuous support. It concludes that while SISKEUDES brings significant improvements, its sustainability requires regular training and the institutionalization of digital competence within the village governance system.